Research on the rebound rule of a pit bottom caused by excavation of typical strata - Yang, Qingyuan; Lu, Yaobo; Wang, Shilu; Wang, Ming; Chen, Song; Wang, Xiaoming (Frontiers in Earth Science, 2024)
In practical engineering, the magnitude of soil unloading rebound is closely related to the physical and mechanical properties of the soil. Therefore, there are significant differences in geological conditions among the different regions. As such, targeted research on the rebound law and calculation methods of foundation pits is needed. This article reports indoor experiments and numerical simulation methods which are used to study the trends and calculation methods of foundation pit rebound based on typical geological conditions in South China. Our findings are as follows. 1) At maximum consolidation stress ranging from 100 kPa to 400kPa, the maximum rebound rate of plain fill soil in typical soil layers is 0.0539–0.0704, the rebound rate of silty clay is 0.0373–0.0528, the rebound rate of coarse sand is 0.0296–0.0343, the rebound rate of gravelly cohesive soil is 0.0159–0.0305, the rebound rate of fully weathered granite is 0.0175–0.0344, and the rebound rate of strongly weathered granite is 0.0170–0.0379. 2) The rebound indices do not change with changes in the unloading ratio or initial consolidation stress. The rebound indices of the soil layer from top to bottom are 0.0143, 0.0119, 0.0077, 0.0096, 0.0083, and 0.0076, respectively, and a formula for calculating the rebound modulus of typical soil layers in South China was proposed. 3) The pore ratio of the soil after the end of the recompression process is lower than that which occurs after the first compression. The difference between the compression porosity ratio of the soil layer from top to bottom and the compression porosity ratio is 0.1, 0.08, 0.02, 0.06, 0.02, and 0.03, respectively. 4) The calculation of the depth of influence by the self-weight stress offset method is based on the theory of eliminating self-weight stress and unloading stress. The calculation depth is not affected by geological conditions, the formula for calculating the rebound modulus is consistent with the formula obtained from experimental research, and the calculation results are in good agreement with the numerical values.